Causes of Primary and Permanent Teeth Extraction in Children Aged 3-12 Years in Mosul City - Aghareed Gh. Mohammed (University of Mosul, College of Dentistry, 2008)
Aims: To establish the different reasons of primary and permanent teeth extraction and the most frequent tooth type extracted among children attending the pedodontic and preventive dentistry clinic at Collage of Dentistry ,Mosul University. Materials and Methods: Out of the 375 pediatric patients aged 3-12 years-old attending pedodontic and preventive dentistry clinic, 130 child patients were selected for this study. The teeth were examined carefully, the tooth that needed to be extracted was recorded to determine the cause of extraction for each tooth according to the criteria gathered and modified from the following researchers, Cahen et al; Kay and Blinkhorn and Cawson. Results: Statistical results showed highly significant difference at p < 0.001 between primary and permanent teeth and the cause of tooth extraction, as extraction due to caries was the main reason for primary tooth extraction while extraction for orthodontic treatment was the major cause for permanent tooth extraction. The first premolar recorded 43.6% this result showed highly significant difference at p < 0.001 compared with other permanent teeth to be extracted, while the first primary molar registered the higher value as an extracted primary tooth type (35.6%) with high significant difference at p < 0.001. Conclusion: Although caries and it is sequelae were the most common causes of premature loss of a primary tooth, an increasing need for tooth extraction for orthodontic treatment in this population of children was observed.